Anti-inflammatory and Antioxidant Activities of Symplocos cochinchinensis (Lour.) Moore ssp. Laurina (Retz.) Nooteb Leaf Extract - Trieu, Ly Hai; Cong Sanh, Pham; Thanh Huy, Nguyen; Ngoc Tuan, Tran; Bich Thao, Lam; Thi Kim Oanh, Le; Thanh Minh, Le; Van Minh, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Symplocos cochinchinensis (S.  cochinchinensis) leaves have been used by Vietnamese in herbal medicines to support the treatment of infirmities. The purpose of this study was to determine some phytochemicals, assess in vitro anti-inflammatory and antioxidant capacities of S. cochinchinensis leaf extract to provide information for further research. The study results show that S. cochinchinensis leaves contain polyphenols, flavonoids, and saponins by chemical reactions and thin layer chromatography profiling. The total polyphenol, flavonoid, and saponin contents were 517.71 ± 19.50 mg GAE/g d. w., 1.12 ± 0.01 mg QE/g d. w., and 32.18 ± 0.24 mg/g d. w., respectively. S. cochinchinensis leaf extract exhibited anti-inflammatory effect via in vitro protein denaturation inhibition, hemolysis inhibition by heat and hypotonicity with IC 50 values of 63.20, 36.32, and 42.55 μg/mL, respectively. S. cochinchinensis leaf extract also displayed antioxidant potential with IC 50 values of 189.09 μg/mL (DPPH inhibition), 60.67 μg/mL (ABTS inhibition), and 140.53 μg/mL (Reducing power). Taken together, S. cochinchinensis leaves have great potential for anti-inflammatory, antioxidant activities and some compounds in pure form should be isolated and studied. Keywords: S. cochinchinensis leaves, anti-inflammatory activity, antioxidant activity [1] L. F. Millani, O. H. Nelsen, P. S. Anderson, S. E. Girardin, Chronic Inflammation: Importance of NOD2 and NALP3 in Interleukin-1 beta Generation, Clinical and Experimental Immunology, Vol. 147, No. 2, 2007, pp. 227-235, https://doi.org/10.1111/j.13652249.2006.03261.x. [2] G. Leelaprakash, S. M. Dass, In Vitro Anti-inflammatory Activity of Methanol Extract of Enicostemma axillare, International Journal of Drug Development & Research, Vol. 3, No. 3, 2011, pp. 189-196. [3] S. Chandra, P. Dey, S. Bhattacharya, Preliminary In Vitro Assessment of Anti-inflammatory Property of Mikania scandens Flower Extract, Journal of Advanced Pharmacy Education & Research, Vol. 2, No. 1, 2012, pp. 25-31. [4] D. B. Kapadiya, B. K. Dabhi, K. D. Aparnathi, Spices and Herbs as a Source of Natural Antioxidants for Food, International Journal of Current Microbiology and Applied Sciences, Vol. 5, No. 7, 2016, pp. 280-288, http://dx.doi.org/10.20546/ijcmas.2016.507.029 [5] C. Sunil, S. Ignacimuthu, P. Agastian, Antidiabetic Effect of Symplocos cochinchinensis (Lour.) S. Moore. in Type 2 Diabetic Rats, Journal of Ethnopharmacology, Vol. 134, No. 2, 2011, pp. 298-304, https://doi.org/10.1016/j.jep.2010.12.018. [6] C. Sunil, P. Agastian, C. Kumarappan, S. Ignacimuthu, In Vitro Antioxidant, Antidiabetic and Antilipidemic Activities of Symplocos cochinchinensis (Lour.) S. Moore bark, Food and Chemical Toxicology, Vol. 50, No. 5, 2012, pp. 1547-1553, https://doi.org/10.1016/j.fct.2012.01.029. [7] K. A. Antu, M. P. Riya, A. Mishra, K. S. Anilkumar, C. K. Chandrakanth, A. K. Tamrakar, A. K. Srivastava, K. G. Raghu, Antidiabetic Property of Symplocos cochinchinensis is Mediated by Inhibition of Alpha Glucosidase and Enhanced Insulin Sensitivity, PLoS One, Vol. 9, No. 9, 2014, pp. 1-13, https://doi.org/10.1371/journal.pone.0105829. [8] B. W. Lee, T. K. Q. Ha, H. T. T. Pham, Q. H. Hoang, V. O. Tran, W. K. Oh, Hydroxyoleoside-type Seco-iridoids from Symplocos cochinchinensis and Their Insulin Mimetic Activity, Scientific Reports, Vol. 9, No. 1, 2019, pp. 1-14, https://doi.org/10.1038/s41598-018-38013-4. [9] Ministry of Healthy, Vietnamese Pharmacopoeia, Fifth Edition, Medical Publishing House, Hanoi, 2017 (in Vietnamese). [10] P. Chumark, K. Panya, S. Yupin, P. Srichan, M. Noppawan, The In Vitro and Ex Vivo Antioxidant Properties, Hypolipidaemic and Antitherosclerotic Activities of Water Extract of Moringa oleifera Lam. Leave, Journal of Ethnopharmacology, Vol. 116, No. 3, 2008, pp. 439-436, https://doi.org/10.1016/j.jep.2007.12.010. [11] T. T. Nguyen, M. O. Parat, M. P. Hodson, J. Pan, P. N. Shaw, A. K. Hewavitharana, Chemical Characterization and In Vitro Cytotoxicity on Squamous Cell Carcinoma Cells of Carica papaya Leaf Extracts, Toxins, Vol. 8, No. 1, 2015, pp. 1-11, https://doi.org/10.3390/toxins8010007. [12] F. Alhakmani, S. Kumar, S. A. Khan, Estimation of Total Phenolic Content, In-vitro Antioxidant and Anti-inflammatory Activity of Flowers of Moringa oleifera, Asian Pacific Journal of Tropical Biomedicine, Vol. 3, No. 8, 2013, pp. 623-627, https://doi.org/10.1016/s2221-1691(13)60126-4. [13] K. Gunathilake, K. Ranaweera, H. Rupasinghe, In Vitro Anti-inflammatory Properties of Selected Green Leafy Vegetables, Biomedicines, Vol. 6, No. 4, 2018, pp. 1-10, https://doi.org/10.3390/biomedicines6040107. [14] N. Pellegrini, M. Serafini, B. Colombi, D. D. Rio, S. Salvatore, M. Bianchi, F. Brighenti, Total Antioxidant Capacity of Plant Foods, Beverages and Oils Consumed in Italy Assessed by Three Different In Vitro Assays, The Journal of Nutrition, Vol. 133, No. 9, 2003, pp. 2812-2819, https://doi.org/10.1093/jn/133.9.2812. [15] M. Oyaizu, Studies on Product of Browning Reaction Prepared from Glucose Amine, The Japanese Journal of Nutrition and Dietetics, Vol. 44, No. 6, 1986, pp. 307-315, https://doi.org/10.5264/eiyogakuzashi.44.307. [16] S. Dharmadeva, L. S. Galgamuwa, C. Prasadinie, N. Kumarasinghe, In Vitro Anti-inflammatory Activity of Ficus racemosa L. Bark using Albumin Denaturation Method, Ayu, Vol. 39, No. 4, 2018, pp. 239-242, https://dx.doi.org/10.4103%2Fayu.AYU_27_18. [17] E. Umapathy, E. J. Ndebia, A. Meeme, B. Adam, P. Menziwa, B. N. N. Chungag, J. E. Iputo, An Experimental Evaluation of Albuca setosa Aqueous Extract on Membrane Stabilization, Protein Denaturation and White Blood Cell Migration during Acute Inflammation, Journal of Medicinal Plants Research, Vol. 4, No. 9, 2010, pp. 789-795, https://doi.org/10.5897/JMPR10.056. [18] C. O. Okoli, P. A. Akah, N. J. Onuoha, T. C. Okoye, A. C. Nwoye, C. S. Nworu, Acanthus montanus: An Experimental Evaluation of the Antimicrobial, Anti-inflammatory and Immunological Properties of a Traditional Remedy for Furuncles, BMC Complementary and Alternative Medicine, Vol. 8, 2008, pp. 1-11, https://doi.org/10.1186/1472-6882-8-27. [19] R. Vadivu, K. S. Lakshmi, In Vitro and In Vivo Anti Inflammatory Activity of Leaves of Symplocos cochinchinensis (Lour) Moore ssp Laurina, Bangladesh Journal of Pharmacology, Vol. 3, No. 2, 2008, pp. 121-124, https://doi.org/10.3329/bjp.v3i2.956. [20] T. B. Ng, F. Liu, Z. T. Wang, Antioxidative Activity of Natural Products from Plants, Life Sciences, Vol. 66, No. 8, 2000, pp. 709-723. https://doi.org/10.1016/s0024-3205(99)00642-6. [21] H. Cory, S. Passarelli, J. Szeto, M. Tamez, J. Mattei, The Role of Polyphenols in Human Health and Food Systems: A Mini-review, Frontiers in Nutrition, Vol. 5, 2018, pp. 1-9, https://dx.doi.org/10.3389%2Ffnut.2018.00087. [22] A. N. Panche, A. D. Diwan, S. R. Chandra, Flavonoids: an overview, Journal of Nutritional Science, Vol. 5, 2016, pp. 1-15, https://dx.doi.org/10.1017%2Fjns.2016.41. [23] C. S. Yuan, C. Z. Wang, S. M. Wicks, L. W. Qi, Chemical and Pharmacological Studies of Saponins with a Focus on American Ginseng, Journal of Ginseng Research, Vol. 34, No. 3, 2010, pp. 160-167, https://dx.doi.org/10.5142%2Fjgr.2010.34.3.160.